2013
DOI: 10.1093/jhered/est089
|View full text |Cite
|
Sign up to set email alerts
|

Mapping of Seed Shattering Loci Provides Insights into Origin of Weedy Rice and Rice Domestication

Abstract: Seed shattering is an important trait that distinguishes crop cultivars from the wild and weedy species. The genetics of seed shattering was investigated in this study to provide insights into rice domestication and the evolution of weedy rice. Quantitative trait locus (QTL) analysis, conducted in 2 recombinant inbred populations involving 2 rice cultivars and a weedy rice accession of the southern United States, revealed 3-5 QTLs that controlled seed shattering with 38-45% of the total phenotypic variation. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
62
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(66 citation statements)
references
References 54 publications
4
62
0
Order By: Relevance
“…Similar reports implicate weedy rice in reducing the yield of cultivated rice by one t ha-1 in Malaysia (Azmi et al, 2012;Chauhan, 2013). Weedy rice is also known as red rice in the USA and arose from Asian domesticated rice; therefore, most weedy rice studies in the US explore the evolutionary basis and population structure of weedy rice (Thurber et al, 2013;Subudhi et al, 2014). Ziska et al (2010) reported that weedy rice shows greater competitive ability in response to rising CO2 levels, thus, deeming it a potentially serious problem of the future.…”
Section: Introductionmentioning
confidence: 76%
“…Similar reports implicate weedy rice in reducing the yield of cultivated rice by one t ha-1 in Malaysia (Azmi et al, 2012;Chauhan, 2013). Weedy rice is also known as red rice in the USA and arose from Asian domesticated rice; therefore, most weedy rice studies in the US explore the evolutionary basis and population structure of weedy rice (Thurber et al, 2013;Subudhi et al, 2014). Ziska et al (2010) reported that weedy rice shows greater competitive ability in response to rising CO2 levels, thus, deeming it a potentially serious problem of the future.…”
Section: Introductionmentioning
confidence: 76%
“…Shattering wild and weedy rice individuals possess well-defined abscission layers at flowering time, which are not present in domestic cultivars (Ferrero and Vidotto 1998;Thurber et al 2011;Akasaka et al 2011). Four shattering genes, sh1, sh2, Sh3, and sh4, have been identified in rice (Subudhi et al 2014). Lin et al (2007) reported the involvement of a single dominant gene, Shattering1 (SHA1), in seed shattering.…”
Section: Seed Shatteringmentioning
confidence: 99%
“…At both loci, weeds share haplotypes with their cultivated progenitors despite significantly different flowering times. For the first time, Subudhi et al (2014) discovered QTL mapping on seed-shattering loci of two rice cultivars and a weedy rice accession in the southern United States. They revealed 3 to 5 QTLs that controlled seed shattering with 38% to 45% of total phenotypic variation between weedy rice and cultivated rice.…”
Section: Origin Distribution and Biotypes Of Weedy Ricementioning
confidence: 99%